Modern Approaches to Assessing the Competitiveness of Commercial Banks ("Journal "U". Economy. Management. Finance.", 2021)
The article describes the characteristics of modern approaches to assessing the competitiveness of commercial banks. The criteria for the classification of these approaches are considered. Along with their content, the emphasis is on describing the shortcomings of existing approaches.
Keywords: banking product; banking service; commercial bank; competitiveness; competition; competitiveness assessment